Antioxidant activity of lawsone and prediction of its activation property on superoxide dismutase - Mohd Noor, Muhammad Noorfaiz; Abdullah, Shazleen Sofea; Ab Hamid, Hasiah; Mohammad Latif, Muhammad Alif; Md Tohid, Siti Farah (Asian Network for Scientific Information (ANSINET), 2021)
Background and Objective: Lawsone, from Lawsonia inermis is reported with high antioxidant properties and is predicted to reduce oxidative stress via binding to the domain of oxidative enzyme Superoxide Dismutase (SOD) receptor. This study is intended to evaluate lawsone’s total antioxidant activity in vitro and the SOD activation property in silico. Materials and Methods: Cytotoxicity of lawsone on A431 and 3T3 cell lines was obtained via MTT assay. Next, FRAP assay was carried out in 2 conditions in vitro : (a) In the absence of cells, and (b) At 200 μM in A431 and 3T3 cells to assess the total antioxidant activity. For in silico studies, AlloSite 2.0 webserver was used to predict the SOD’s allosteric site, followed by AutoDock Tools (ADT) for molecular docking and finally interaction analysis via PyMOL software, ProteinsPlus and PLIP webservers. Results: IC50 of lawsone on the A431 cell line was determined at 3650 μM while no IC50 was detected on the 3T3 cell line. Lawsone exhibited the total antioxidant activities in the absence of cells, in A431 and 3T3 cell lines at 4.04±0.18, 94.41±1.21 and 93.50±8.48 μM, respectively. In silico results showed that lawsone binds to 2 allosteric regions A and B of SOD1, with binding affinities of -7.3 and -6.6 kcal mol–1, respectively. Molecular docking results illustrated several hydrophobic interactions and 4 hydrogen bondings between lawsone and SOD. Conclusion: Lawsone exhibited a low range increment in total antioxidant activity at low concentration and can excellently bind to the allosteric sites of SOD.